A new interspecific hybrid of Torenia obtained through ovule culture - Laojunta, Tanapoom; Narumi-Kawasaki, Takako; Takamura, Takejiro; Fukai, Seiichi (Horticulture, environment and biotechnology, 2019)
Torenia is one of the most popular summer bedding plants in Japan. Commercially available hybrids are assumed to be interspecific hybrids derived from T. fournieri , T. concolor , and T. baillonii . Use of new Torenia species is required to produce novel flower types of interspecific hybrids. Three species from Thailand, T. bicolor , T. hirsutissima , and T. siamensis , were selected and crossed with T. fournieri , T. concolor , and T. baillonii . The chromosome number of six Torenia species varied from 2n = 16 to 2n = 34. Mature seeds were obtained from only 3 of 30 reciprocal cross combinations: T. fournieri × T. bicolor , T. fournieri × T. baillonii , and T. bicolor × T. baillonii . Ovule culture was applied to overcome the interspecific crossing barrier of Torenia , ovule culture was applied. Swollen ovules (250) were taken from pods at 10 days after crossing and cultured on MS medium. Progenies were obtained in 14 cross combinations, through ovule culture. This is the first interspecific Torenia hybrid obtained using T. bicolor , T. hirsutissima , and T. siamensis. The hybridity of all the obtained plants was confirmed using PCR–RFLP analysis of rDNA. The obtained hybrids showed intermediate morphological characteristics and pigmentation of floral organs between parents. This study shows that ovule culture is a powerful tool for overcoming the crossing barrier in interspecific crosses in Torenia.